2009
DOI: 10.3390/molecules14031098
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols with Antiulcerogenic Action from Aqueous Decoction of Mango Leaves (Mangifera indica L.)

Abstract: This study was designed to determine the gastroprotective effect of a Mangifera indica leaf decoction (AD), on different experimental models in rodents. The administration of AD up to a dose of 5 g/kg (p.o.) did not produce any signs or symptoms of toxicity in the treated animals, while significantly decreasing the severity of gastric damage induced by several gastroprotective models. Oral pre-treatment with AD (250, 500 or 1000 mg/kg) in mice and rats with gastric lesions induced by HCl/ethanol, absolute etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 56 publications
0
52
0
Order By: Relevance
“…Considering the individual plant components of DAS-77, Severi et al [25] reported the gastroprotective effect of the aqueous decoction of Mangifera indica leaves in several ulcer models in rats. Phenolic compounds consequently isolated from the extract include mangiferin and cglucosylbenzophenone.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the individual plant components of DAS-77, Severi et al [25] reported the gastroprotective effect of the aqueous decoction of Mangifera indica leaves in several ulcer models in rats. Phenolic compounds consequently isolated from the extract include mangiferin and cglucosylbenzophenone.…”
Section: Discussionmentioning
confidence: 99%
“…Many evidence support that mango also possesses gastro-protective effects. To this purpose, Severi et al [23] showed that a Mangifera indica leaf decoction attenuated in mice the gastric damage induced by HCl/ethanol. This effect seems to be related to mangiferin and benzophenone glycoside, the main bioactive molecules present in leaf decoction.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%
“…13 Two main phenolic compounds were isolated from M. indica leaves aqueous decoction, specifically mangiferin and C-glucosylbenzophenone. 14 Six different extracts from the leaves of Mangifera indica was extracted. In that study, a hexane-ethyl acetate extract was characterized by gas chromatography-mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%